Etika Berkomunikasi di Era Digital: Eksplorasi Pola Interaksi dan Konten Berbahaya di Media Sosial - Rilia, Cintana Aisyah; Malid, Abdul; Sari, Rika Puspita; Amiruddin, Amiruddin (VISA: Journal of Vision and Ideas, 2024)
Social media platforms have developed into important instruments for social interaction, communication, and information gathering. Through a series of routine actions, ethics provides humans with experience of how other people live their lives. This research method uses clustering data mining. Ethics can help human behavior in making judgments and acting in accordance with their philosophy of life. When deciding what to understand and what to do, ethics is a very useful tool. Because ethics can be applied to every aspect of life, ethics can be categorized into several areas based on facets or aspects of human life. Relations between people will be positive and friendly if there is good communication ethics. Therefore, social media users should think about the implications of the material and comments they publish. Additionally, respect and empathy for other individuals is an important component of social media communication etiquette. If communication ethics are not understood, miscommunication will arise, giving rise to debates and conflicts that can damage social harmony.